Experiencias en el uso del internet en estudiantes de enfermería de una universidad privada - Cabrejos Solis, Sandra Nevenka (2021)
Objective: To describe and understand the experiences in the use of the Internet of the students of the Nursing School of the I and II cycle of a private university of Chiclayo, 2019. Method: This research was qualitative with an exploratory descriptive approach, made up of all university students belonging to the I and II 2019 cycle II of the nursing school of the Catholic University Santo Toribio de Mogrovejo, who took all their courses according to their plan of studies, singles, their ages ranged from 17-20 years, an adolescent and young population. The sample size was 12 regular nursing students, and it was determined by the saturation and redundancy data technique. To obtain data, the semi-structured interview was applied in depth, prepared by the researcher and validated by expert judgment. The data was processed with content analysis, ethical principles and scientific rigor were kept. Main results: Two categories: a) Use of the Internet as an educational support: virtual campus, information search and group work and b) Use of the Internet as a means of communication and entertainment: risks and repercussions. General conclusion: Nursing students see the internet as a very important tool in their training, communication and university entertainment, but at the same time they experienced repercussions on their health (sleep pattern disorders such as insomnia, red and tired eyes, fatigue physical), as in the social (cyberbullying). Descriptors (indicating unique identifier): Experience (D008016) Internet (D020407), nursing students (D013338).